A Guide for Fostering Parent–Child Math Talk and Play During Shared Book-Reading Across Diverse Genres - Deborah Bergman Deitcher; Michelle M. Neumann (Education Sciences)
This theoretical paper expands upon previous research and proposes a guide for promoting mathematical talk and play through shared book reading (SBR), with a focus on the home environment. Building on a previously developed classroom-based model, this article describes a design-based research approach to extend the guide to including diverse literary genres—such as narrative, informational, multicultural, and math-specific books in a home setting. Parent–child shared book-reading in authentic contexts can provide a rich platform for “math talk”, where references are made to mathematical words, concepts, and content, and may support children’s mathematical skills. SBR with quality children’s literature can play a promising role in motivating and engaging children’s interest and pleasure in both reading and mathematics. However, few studies have explored this with diverse literary genres in the home setting, as the main focus has been in the classroom and using books specifically written to teach math content such as counting or sorting books. The proposed guide provides direction and practical examples for fostering parent–child math talk and play activities that can be used to extend concepts covered during the SBR. The potential application of the SBR guide, and how it can encourage parent–child talk to support a full range of mathematical concepts, encourage home-preschool collaboration, promote effective SBR techniques, and facilitate parent–child conversations about math in new and confident ways is discussed.